2022
DOI: 10.1111/pan.14459
|View full text |Cite
|
Sign up to set email alerts
|

Modified fluid gelatin 4% for perioperative volume replacement in pediatric patients (GPS): Results of a European prospective noninterventional multicenter study

Abstract: Introduction Modified fluid gelatin 4% is approved for use in children, but there is still a surprising lack of clinical studies including large numbers of pediatric patients. Therefore, we performed a European prospective noninterventional multicenter study to evaluate the use of a modified fluid gelatin 4% in saline (sal‐GEL) or an acetate‐containing balanced electrolyte solution (bal‐GEL) in children undergoing major pediatric surgery. Aims The primary aim was to assess the indications and dosing of modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…11 This concept has been proven to be suitable for electrolyte solutions, but our study showed that it is probably not appropriate for gelatin-containing solutions for the TA B L E 2 Concentrations of osmotically active molecules and measured osmolality after in-vitro dilution of human blood with gelatin (GEL) or albumin (ALB) respectively, presented as mean ± SD Measuring the osmolality by freezing point depression is the gold standard, but, because of the observational study design of the GPS study, this was not possible in the in-vivo part. 5 Therefore, we calculated the osmolality using a modified version of Zander's formula, which showed excellent concordance with measured osmolality. 6 The results of our in-vitro experiment can be explained by simple dilution.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…11 This concept has been proven to be suitable for electrolyte solutions, but our study showed that it is probably not appropriate for gelatin-containing solutions for the TA B L E 2 Concentrations of osmotically active molecules and measured osmolality after in-vitro dilution of human blood with gelatin (GEL) or albumin (ALB) respectively, presented as mean ± SD Measuring the osmolality by freezing point depression is the gold standard, but, because of the observational study design of the GPS study, this was not possible in the in-vivo part. 5 Therefore, we calculated the osmolality using a modified version of Zander's formula, which showed excellent concordance with measured osmolality. 6 The results of our in-vitro experiment can be explained by simple dilution.…”
Section: Discussionmentioning
confidence: 82%
“…Measuring the osmolality by freezing point depression is the gold standard, but, because of the observational study design of the GPS study, this was not possible in the in‐vivo part 5 . Therefore, we calculated the osmolality using a modified version of Zander's formula, which showed excellent concordance with measured osmolality 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations